2012
DOI: 10.1007/s10554-012-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular regional and global systolic function is diminished in patients with pulmonary arterial hypertension: a 2-dimensional ultrasound speckle tracking echocardiography study

Abstract: The purpose of the study is to evaluate right ventricular (RV) regional and global systolic function in patients with pulmonary arterial hypertension (PAH) by 2-dimensional ultrasound speckle tracking echocardiography (STE) and explore the impact of pulmonary artery systolic pressure (PASP) and pulmonary vascular resistance (PVR) on RV systolic function. 42 patients with PAH and 31 healthy controls were included in this study. RV longitudinal peak systolic strain (LS) and strain rate (LSRs) were measured at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 20 publications
1
38
1
2
Order By: Relevance
“…Based on these reports, in clinical RV evaluation, measurement of LS has been widely used and LS is currently recognized as the most useful strain variable in RV evaluation. 14,17,19) However, in terms of RV evaluation in the rat model, our results showed that only CS, but not LS, has significant differences although the reproducibility of LS and CS was similar. This result goes against our expectation.…”
Section: ) 67mentioning
confidence: 55%
See 1 more Smart Citation
“…Based on these reports, in clinical RV evaluation, measurement of LS has been widely used and LS is currently recognized as the most useful strain variable in RV evaluation. 14,17,19) However, in terms of RV evaluation in the rat model, our results showed that only CS, but not LS, has significant differences although the reproducibility of LS and CS was similar. This result goes against our expectation.…”
Section: ) 67mentioning
confidence: 55%
“…Pirat, et al 16) used STE to evaluate RV function in 48 patients with PH and 19 age-matched controls and reported that STE can provide angle independent quantitation of RV function. Li, et al 17) evaluated 42 patients with PH and 31 healthy controls using STE and concluded that STE can identify impaired RV function. Hardegree, et al 18) assessed 50 patients with PH before and after the initiation of therapy.…”
Section: ) 67mentioning
confidence: 99%
“…60 While RV strain reflects myocardial performance, it is influenced by increased afterload and will decrease with increasing RV afterload. 61 RV global longitudinal peak systolic strain and strain rate were significantly impaired in adults with PH, compared to controls, 62 with RV systolic strain most altered in patients with severe PH, when compared with patients with mild PH. 62 Significant correlations between RV strain and strain rate and mPAP were found in adult PAH patients.…”
Section: Rv Fractional Area Changementioning
confidence: 94%
“…61 RV global longitudinal peak systolic strain and strain rate were significantly impaired in adults with PH, compared to controls, 62 with RV systolic strain most altered in patients with severe PH, when compared with patients with mild PH. 62 Significant correlations between RV strain and strain rate and mPAP were found in adult PAH patients. 63 The important value of serial measurement of RV systolic strain in the prediction of long-term prognosis was also shown in patients with PH.…”
Section: Rv Fractional Area Changementioning
confidence: 94%
“…Indeed, although standard 2D transthoracic echocardiography has provided merely 3 potential treatment goals-preserved tricuspid annulus systolic excursion, normal right atrial area, and the absence of pericardial effusion-modern right heart echocardiography has potentially more to offer. [10][11][12][13][14][15][16][17][18][19][20] Of note, in their study, Ryo et al did not follow this direction but limited the assessment to rather rudimental estimation of RV volumes, simply expecting better precision of the measurements assisted by 3D wall motion tracking when compared with traditional 2D echocardiography. Similar to CMR, this still required manual tracing of endocardial and epicardial borders.…”
Section: See Article By Ryo Et Almentioning
confidence: 95%